The quest for immunotherapy in atherosclerosis: CANTOS study, interleukin-1β and vascular inflammation (2017)
espite the monumental efforts directed into studying and describing the pathways, factors, genetic predisposition, and target-specific pharmacotherapy to atherosclerosis, ischemic heart disease, thrombotic cerebrovascular disease and peripheral artery disease are still responsible for 50% of all the deaths occurring in the developed world. The quest for a clear pathophysiology into atherosclerosis began with von Rokitansky’s incrustation theory, which evolved into the crucial role of platelets and thrombogenesis during acute coronary syndromes (1). Next, came the irritation theory postulated by Virchow, which detailed the presence of leukocytes in atherosclerotic plaques, suggesting the presence of chronic inflammation and progressive vessel deformation (1). By 1904, the term atherosclerosis was coined by Felix Jacob Marchand and 9 years later Nikolai Anichkov published that cholesterol alone can induce the vascular changes associated with atherosclerosis (1). The impeccable work performed by Anichkov and his team, paved the way to the current understanding and clinical logic used in current cardiovascular medicine (the lipid hypothesis), which for the longest period focused mainly in plasma lipids as sole culprits for atherogenesis. Genetic connection between cholesterol and heart disease came in 1939, when Müller described families with severe hypercholesterolemia and early onset cardiac disease and death (2). The recognition of hereditary hyperlipidemias and their characteristics, cemented the role on cholesterol in cardiovascular risk, along with the findings from the epidemiological mammoth, the Framingham Heart Study (3). At some point, the lipid hypothesis was “universally recognized as a law” [2002] (4), and as such, it dominated pharmacotherapy development in cardiovascular medicine.